Chapter 12. Advanced Analytical Techniques (Analytical Methods for Drug Development, 2025)
AuthorDr. Shashikala MetriAssociate Professor, Department of Pharmacognosy, Gokaraju Rangaraju College of Pharmacy, Bachupally, Hyderabad, Telangana, IndiaAbstractAdvanced analytical technologies push pharmaceutical analysis boundaries through innovative approaches and instrument combinations. Hyphenated techniques like LC-MS, GC-MS, and LC-NMR couple separation with identification, enabling structural elucidation, metabolite identification, and complex mixture analysis with sensitivity and specificity unattainable by individual methods. Process analytical technology implements near-infrared spectroscopy, Raman spectroscopy, and acoustic emission for real-time monitoring of manufacturing processes, enabling process understanding and control without offline sampling. Real-time monitoring systems integrate sensors, data acquisition, and feedback controls for continuous manufacturing with immediate corrective actions. Emerging technologies include portable analytical devices for point-of-use testing, microfluidic systems for reduced sample volume, 3D imaging for spatial distribution analysis, and artificial intelligence for complex data interpretation. Implementation challenges involve validation techniques, regulatory acceptance, and integration with existing systems.Keywords: Hyphenated Chromatography Techniques, Real-Time Process Monitoring, Raman Spectroscopy, Continuous ManufacturingVIEW PDF